A DFT study on the structure and radical scavenging activity of newly synthesized hydroxychalcones. (12th December 2012) - Xue, Yunsheng; Zhang, Ling; Li, Yanli; Yu, Ding; Zheng, Youguang; An, Lin; Gong, Xuedong; Liu, Yi
<x xml:space="preserve">Abstract</x> Quantum‐chemical computations based on the density functional theory have been employed to study the relation between the structure and the radical scavenging activity of six newly synthesized hydroxychalcones. The three main working mechanisms, hydrogen atom transfer (HAT), stepwise electron‐transfer‐proton‐transfer, and sequential‐proton‐loss‐electron‐transfer (SPLET), were investigated, and the O–H bond dissociation enthalpy, ionization potential, proton dissociation enthalpy, and electron transfer energy parameters were computed in the gas phase and in solvents using PCM model. The geometry structure, radical, electron character, and the frontier molecular orbital were analyzed to explore the key factors that influence the radical scavenging activity of the hydroxychalcones. Results indicated that 3, 4‐dihydroxychalcone (6) possessing the catechol functionality is expected to be more efficient hydrogen atom and proton donor than others. The theoretical results confirm the important role of the B‐ring and shed light on the role of the o‐dihydroxy (catechol) moiety in the antioxidant properties of hydroxychalcones. In addition, the calculated results are in good agreement with experimental values. It was found that HAT is the most favored mechanism for explaining the radical‐scavenger activity of hydroxychalcone in the gas phase, whereas SPLET mechanism is thermodynamically preferred pathway in aqueous solutions. Copyright © 2012 John Wiley & Sons, Ltd.